When x is equal to -1:
f(-1)=6(-1)-3
=-7-3
=-10
y=-10
When x is equal to 0:
f(0)=6(0)-3
=0-3
=-3
y=-3
When x is equal to 1:
f(1)=6(1)-3
=6-3
=3
y=3
When x is equal to 2:
f(2)=6(2)-3
=12-3
=9
y=9
Answer:C
Step-by-step explanation:
Answer:
C.
Since the square root of 20 is around 4.5, we know that ≈4.5 is almost at the half mark between 4 and 5 on the number line.
Answer:
3520
Step-by-step explanation:
33-11=22
40 times 22=880
880 times 4=3520
The total weight of candies is unknown. Let x = the total weight of candies.
"One student ate 3/20 of all candies and another 1.2 lb":
The first student ate (3/20)x plus 1.2 lb which is 0.15x + 1.2.
"The second student ate 3/5 of the candies and the remaining 0.3 lb."
The second student ate (3/5)x and 0.3 lb which is 0.6x + 0.3.
Altogether the 2 students ate 0.15x + 1.2 + 0.6x + 0.3.
That was all the amount of candies, so that sum equals x.
0.15x + 1.2 + 0.6x + 0.3 = x
Now we solve the equation for x to find what the total amount of candies was.
0.75x + 1.5 = x
-0.25x = -1.5
x = 6
The total amount of candies was 6 lb.
The first student ate 0.15x + 1.2 = 0.15(6) + 1.2 = 0.9 + 1.2 = 2.1, or 2.1 lb of candies.
The second student ate 0.6x + 0.3 = 0.6(6) + 0.3 = 3.6 + 0.3 = 3.9, or 3.9 lb of candies.
Answer: The first student ate 2.1 lb of candies, and the second student ate 3.9 lb of candies.